A parametric study on the mechanical and thermal stability of corrugated-core sandwich plates. (April 2020) - Zamanifar, Hossein; Sarrami-Foroushani, Saeid; Azhari, Mojtaba
Abstract: Mechanical and thermal buckling of corrugated-core sandwich plates is investigated in this study. To consider the effect of shear deformations, the first-order shear deformation theory is applied to the finite strip method. The validity of the proposed method is evaluated by comparing the results with those presented by previous research. Various boundary conditions and different loading types, as well as the geometric parameters affecting the buckling loads and critical temperatures are explored and evaluated. To the authors' best knowledge, investigation of the effective geometric parameters, convergence process and different boundary conditions are discussed for the first time using finite strip method.